Development and evaluation of an implementation strategy for the German guideline on community-acquired pneumonia. Issue 6 (13th April 2010) - Schnoor, M; Meyer, T; Suttorp, N; Raspe, H; Welte, T; Schäfer, T; ,
Abstract : Background: Data of the German Competence Network for Community-Acquired Pneumonia showed a gap between the recommendations of the national guideline for management of community-acquired pneumonia (CAP) and the routine care. We developed and evaluated an implementation strategy to improve the quality of care of patients with CAP. Method: A prospective, randomised, controlled trail was conducted within CAPNETZ. In four local clinical centres (LCC), the guideline was implemented by different strategies. The other four LCC served as control group. Indicators for guideline adherence comprised initial site of treatment, initial antibiotic treatment and duration of antibiotic treatment. As patient-related factors, we assessed the effect of guideline implementation on 30-day mortality and length of hospital stay. Results: Active guideline implementation yielded an increased proportion of guideline adherence to the length of antibiotic treatment in outpatients (+9.2%), the recommended antibiotic treatment (+5.6%) and duration of antibiotic treatment in inpatients (+5.0%) compared with baseline. In contrast, the proportion of patients in the control group, treated according to the guideline, decreased in the same period by 7.9%, 2.9% and 4.7%, respectively. None of these results was statistically significant. Decrease of CAP-related mortality was higher in the intervention group compared with the control group (2.9% vs 0.5%, ns). Conclusion: This study showed improvements in the process of care after implementation of a guideline for treating CAP. Further strategies, such as quality improvement cycles and medical practice audits, may enhance this effect.